Senescence Physiology or Pathology - Dorszewska, Jolanta; Kozubski, Wojciech (IntechOpen, 2017)
In the second half of the twentieth century, life expectancy was prolonged, and the number of elderly people increased. The effect of population aging increases in the frequency of neurodegenerative diseases such as Alzheimer's and Parkinson's diseases, epilepsy, and stroke. Also, a higher incidence of infections, autoimmune diseases, and malignant cancers is observed in elderly people. The aging process is difficult to define. Are physiological changes in elderly people controlled by specific genes? Is aging process a pathophysiology affecting different organs with different severity? Finding answers to these questions may help prevent age-related diseases and improve the quality of life of old people. This book was made as a compendium on contemporary challenges in senescence.